Islamic Educational Values in Serat Wedhatama by KGPAA Mangkunegara IV - Setiawan, Adie; Indianto S., Dimas; Triyatno, Agung; Wiyono, Teguh (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
The impact of globalization is one of the factors that can influence the world of education in general and Islamic education in particular. In the era of information technology that continues to develop, it has led to the loss of national identity. Therefore, it is necessary to strengthen the values of Islamic education which are enriched with local wisdom values to become a guide to life, especially in behavior for the nation's generation in accordance with national identity. One of the values of local wisdom that can be explored in depth is content Serat Wedhatama. Serat Wedhatama contains teachings about nobility in human life, for example teachings about polite and wise behavior. This research aims to analyze and describe the values of Islamic education in Serat Wedhatama by Kanjeng Gusti Pangeran Adipati Arya (K.G.P.A.A.) Mangkunegara IV. This type of research uses a type of library research using a qualitative descriptive approach. This research uses Serat Wedhatama, one of the components of piwulang fiber which is used as a material based on Islamic religious education. In analyzing the data, researchers used Miles and Faisal's strategic analysis techniques with data reduction, data presentation, inference and verification steps. Data collection techniques in this research used library, listening and note-taking techniques. Meanwhile, the data inspection technique used in this research is to increase persistence. Then the data analysis technique used in this research is method content analysis or content analysis. The results of this research show that Serat Wedhatama by Kanjeng Gusti Pangeran Adipati Arya (K.G.P.A.A) Mangkunegara IV there are three values of Islamic education, namely First the value of faith education in God with soul worship and taste. Second, the value of mahmudah moral education (praiseworthy morals) and avoiding mazmumah morals (reprehensible morals). Third, the educational value of ablution, prayer, dhikr, fasting, zakat, and reading the Qur'an. Teaching Serat Wedhatama also has relevance to Islamic education, namely the similarity of the concept of the teaching of life values with Islamic education such as: teachings about divinity, scientific concepts, and how to obtain knowledge of moral teachings, nobility of character and perfection of life.